Strategi Penguatan Keberlangsungan Usaha Melalui Edukasi Literasi Keuangan: Studi Pada Sentra Indutri Tempe Sanan - Mega Noerman Ningtyas; Novi Lailiyul Wafiroh (Fakultas Ekonomi, UIN Maliki Malang, 2023)
Education to improve the understanding of financial literacy in MSMEs is one of the efforts that can be carried out to enrich their knowledge. This knowledge will be useful for their business, especially for sustainability of their business. This research was conducted at the Tempe Sanan Industrial Center, Malang using a qualitative method, that is interviews. The results of the study show that not all business actors have sufficient financial literacy, especially if it is related to the investment context. However, business actors are considered sufficient to have a good financial attitude but not for things such as: making budgets, monitoring cash flows, and planning business protection. This is because business actors are too busy with their business operations so they do not have enough time to do the things above..